(untitled) (Third Sector Social Economic Review, 2017)
There are various social contract theories about the way people come together and live in a society. Locke emerges as one of these theorists. The idea that distinguishes Locke from other theorists is that he describes natural human as neither good nor bad. He laid the foundations of modern social structure analysis with an emphasis on reason. Each of the contemporary sociological theories emphasizes that people come together to accomplish a set of goals and that society continues to function as long as these goals are realized. In this framework, theories such as functionalism, mental choice, conflict, phenomenology and symbolic interactionism emphasize the individual’s use of the mind in the context of social acceptance and achievement of goals. Each theory tries to establish the main purpose of individual action. Locke’s thoughts include views that could be source for all these theories. Locke’s definition of individual freedoms, especially on the basis of private property, has the utmost importance in shaping today’s liberal state and social structure.